Orgasmic Headache: a differential diagnosis with spontaneous subarachnoid hemorrhage (sSAH) - Freitas, Melissa Fernandes Vilela de; Reis, Taianara Sampaio; Filho, Amauri Pereira da Silva; Romano, Danielle Cortellazzi Colonna; Nakamura, Gabriela Yumi; Karpejany, Natália Rebeca Alves de Araújo; Batista, Sabrina Borges (Headache Medicine, 2024)
INTRODUCTION: Orgasmic headache (OH) is a rare, sudden and severe headache that occurs at the time of or shortly after an orgasm. This type of primary headache associated with sexual activity typically lasts from 1 minute to 24 hours with severe pain and up to 72 hours with mild pain. OH can manifest at any sexually active age and is more common in men than in women. Studies have shown that up to 40% of cases of primary headache associated with sexual activity exhibit a chronic pattern lasting over a year. When diagnosing, it is crucial to meticulously rule out other serious conditions such as subarachnoid hemorrhage, arterial dissection, and reversible cerebral vasoconstriction syndrome. OBJECTIVE: Describing and recognizing a rare pathology. CASE REPORT: We present the case of a 38-year-old female university professor from Campina Grande, Paraíba, with no significant medical history. The patient complained of sudden, severe, explosive headache during sexual activity, characterized as holocranial and of high intensity, accompanied by nausea and vomiting. The headache persisted for up to 24 hours post-activity but with reduced intensity. The patient reported partial relief with over-the-counter analgesics. She experienced 6 similar episodes over the last 3 months, which caused fear and led to sexual abstinence. General and neurological physical examinations were unremarkable. Diagnostic tests including cranial CT scan, cranial MRI, angiotomography, and ambulatory blood pressure monitoring (ABPM) showed normal results. Based on the clinical presentation and investigative findings, a diagnosis of orgasmic headache was made. Prophylactic treatment with indomethacin before sexual activity was initiated. CONCLUSION: Accurate diagnosis of orgasmic headache is crucial to distinguish it from serious conditions like spontaneous subarachnoid hemorrhage (sSAH). Excluding secondary causes ensures appropriate treatment, involving adjustments in sexual behavior and prophylactic medications based on headache frequency and severity, thus avoiding unnecessary interventions for more severe conditions.